2022
DOI: 10.3390/foods11060787
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation of Chemical Characteristics in Young Marselan (Vitis vinifera L.) Red Wines from Five Regions of China

Abstract: The environmental conditions of wine regions determine the flavor characteristics of wine. The characterization of the chemical composition and sensory profiles of young Marselan wines from five wine-producing regions in China was investigated by gas chromatography-mass spectrometry (MS), high-performance liquid chromatography–triple-quadrupole MS/MS and descriptive analysis. Young Marselan wines can be successful discriminated based on concentrations of volatile compounds, but not phenolic compounds, by ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
3
4
0
Order By: Relevance
“…At the end of fermentation ( Supplementary Table S3 ), Ethyl caprylate (banana, pear, flower), Ethyl caprate (pear, brandy), Ethyl caproate (apple, pineapple, banana), isoamyl acetate (banana) and Ethyl 9-decenoate (fruity) will bring pleasant floral and fruity aromas to the wine. This accords with previous reports [ 35 ].…”
Section: Resultssupporting
confidence: 94%
“…At the end of fermentation ( Supplementary Table S3 ), Ethyl caprylate (banana, pear, flower), Ethyl caprate (pear, brandy), Ethyl caproate (apple, pineapple, banana), isoamyl acetate (banana) and Ethyl 9-decenoate (fruity) will bring pleasant floral and fruity aromas to the wine. This accords with previous reports [ 35 ].…”
Section: Resultssupporting
confidence: 94%
“…As for C13-norisoprenoids derived from grape carotenoids, β -damascenone was the most important compound with high OAV ranging from 192.73 to 388.37 in Chinese Dornfelder wines, of which the highest concentration was found in the JP wine ( Table 3 ). It was consistent with the study of Marselan red wines that a higher concentration of β -damascenone was found in wines from the JP region than in wines from the NFTM region ( Lan et al, 2022 ). Another study of Cabernet Sauvignon from different Chinese viticulture regions also found that grape berries from the JP region (Yantai City) had higher contents of C13-norisoprenoids than those from the NFTM region (Wujiaqu County) and the EFHM region (Yongning County) ( Xie, Lei, Wang, Wang, Ren, & Zhang, 2018 ).…”
Section: Resultssupporting
confidence: 92%
“…There is a distinct climate difference among these three premium Dornfleder wine-producing regions in China. The Northern Foothills of Tianshan Mountains (NFTM) and the Eastern Foothills of Helan Mountains (EFHM) are both continental semi-arid climate with longer sunlight duration, higher diurnal temperature range, and photosynthetically active radiation (PAR) compared to the Jiaodong Peninsula (JP), which is located in the eastern coast of China and has a temperate monsoon climate with more rainfall ( Lan et al, 2022 , Jiang et al, 2013 ). Meanwhile, slightly shorter sunlight duration and PAR but higher average temperature and rainfall were found in the EFHM region than the NFTM region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, grape pomaces have a high organic carbon content (31–54%), which is responsible for water pollution and foul odors, moreover pests and tannins, among other compounds, may affect the nearby flora and animals [ 6 , 7 ]. Different grape varieties are cultivated all over the world depending on the geographical distribution, climate changes, temperature trends, and the type of soil [ 8 , 9 ] and several studies confirmed that their content in bioactive molecules differs across varieties, especially between the red and white ones [ 10 ]. Among the different varieties, Marselan, Syrah, and Cabernet Franc are cultivated across vineyards worldwide [ 11 ], while Asswad Karech and Obeidi are Lebanese species.…”
Section: Introductionmentioning
confidence: 99%